Electrical, thermal and optical characteristics of plasma torch - Hussain, Ali A-K. (Iraqi Journal of Physics, 2019)
Non thermal argon plasma needle at atmospheric pressure was constructed. The experimental set up was based on simple and low cost electric components that generate electrical field sufficiently high at the electrodes to ionize various gases which flow at atmospheric pressure. A high AC power supply was used with 9.6kV peak to peak and 33kHz frequency. The plasma was generated using two electrodes. The voltage and current discharge waveform were measured. The temperature of Ar gas plasma jet at different gas flow rate and distances from the plasma electrode was also recorded. It was found that the temperature increased with increasing frequency to reach the maximum value at 15 kHz, and that the current leading the voltage, which demonstrates the capacitive character of the discharge. The electron temperature was measured at about 0.61 eV, and we calculated the electron number density to be 4.38×1015 cm-3.